Challenges and Opportunities for Data-Intensive Computing in the Cloud. - Jung, Eun-Sung; Kettimuthu, Rajkumar (Computer (00189162), 2014)
Now running mostly on high-performance computers, data-intensive applications pose several important challenges as they move toward cloud deployment.